Negarawan dari Desa Cinta : biografi R.H. Moh. Sanusi Hardjadinata, 1914-1995 - Lubis, Nina H. (Nina Herlina), 1956- ([Bandung] : Satya Historika, 2003)
Biography of the late Mohammad Sanusi Hardjadinata, politician and the former Governor of Jawa Barat Province.
Includes bibliographical references (p. 343-345) and index.
Keywords: Hardjadinata, Moh. S. -- 1914-1995.; Politicians -- Indonesia -- Biography; Governors -- Indonesia -- Jawa Barat -- Biography; Jawa Barat (Indonesia) -- Biography